Peningkatan Kualitas Laporan Keuangan UMKM Melalui Kompetensi Akuntansi dan Literasi Keuangan dengan Adopsi Aplikasi Digital sebagai Variabel Moderasi pada UMKM di Kecamatan Medan Amplas - Mhd Rizaldy Wibowo; Reza Hanafi Lubis; Rukmini Rukmini; Nova Azahra; Sri Murniyanti (Institut Nalanda, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia's economy, but because the quality of their financial reporting is still low, it becomes one of the obstacles in business decision-making and access to financing. This study aims to analyze the effect of accounting competence and financial literacy on the quality of MSME financial reports, as well as to test the role of digital application adoption as a moderating variable. The research approach used is quantitative with a survey method. Data was collected through a Likert-scale questionnaire distributed to 125 MSME actors in Medan Amplas District. Data analysis was conducted using the Structural Equation Modeling – Partial Least Squares (SEM-PLS) method. The research is expected to show that accounting competence and financial literacy have a positive impact on the quality of financial reports, and that adopting digital applications strengthens this relationship. This study is at technology readiness level (TRL) 3. It aligns with SDG 4 – Strengthening Knowledge and Literacy. Improving the quality of financial reports will increase access to financing and investment for SMEs, in line with SDG 8 – Decent Work and Economic Growth. Digitalizing financial reports is a form of innovation that enhances the competitiveness of SMEs. Developing this infrastructure aligns with SDG 9 – Industry, Innovation, and Infrastructure. This research supports Asta Cita-6 of the President of Indonesia, regarding (Strengthening the Empowerment of SMEs and Cooperatives), which aims to boost economic independence and the competitiveness of national SMEs in a sustainable way.